Improved microwave method for measuring the dynamic parameters of gasification of condensed materials - Podshivalov, A. I.; Grishin, Yu. A.; Kiskin, Alexander B.; Zarko, Vladimir E. (Combustion, explosion, and shock waves)
A new microwave technique for measuring the transient gasification rate is described. A feature of the technique is that the mass loss during gasification is determined based on measurements of the time-varying resonant frequency of the microwave resonator with the test sample by sequentially recording the resonant characteristics of the sensor. This ensures independence of the measurement results from the change in the Q-value of the resonator during gasification of the propellant sample. A sensor prototype which is a coaxial resonator in which the sample under study is placed in the region of maximum electric field has been tested. Experiments have shown that the sensitivity (the ratio of the change in resonant frequency to the change in the inner diameter of the sample) of the new sensor design is two to four times higher than that of the previous sensor model.